2015
DOI: 10.1111/jsr.12283
|View full text |Cite
|
Sign up to set email alerts
|

Associations of disordered sleep with body fat distribution, physical activity and diet among overweight middle‐aged men

Abstract: SUMMARYThis cross-sectional study aimed to investigate whether body fat distribution, physical activity levels and dietary intakes are associated with insomnia and/or obstructive sleep apnea among overweight middleaged men. Participants were 211 Finnish men aged 30-65 years. Among the 163 overweight or obese participants, 40 had insomnia only, 23 had obstructive sleep apnea only, 24 had comorbid insomnia and obstructive sleep apnea and 76 were without sleep disorder. The remaining 48 participants had normal we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 43 publications
3
71
0
5
Order By: Relevance
“…Similar results were found with respect to the association between carbohydrate intake and sleep quality in men (17). Individuals with disordered sleep (insomnia, obstructive sleep apnea, or a combination of the 2) assessed by questionnaires reported lower total carbohydrate intakes than did normal-weight individuals who were free from sleep disorders.…”
Section: Dietary Patterns and Sleep Qualitysupporting
confidence: 72%
See 2 more Smart Citations
“…Similar results were found with respect to the association between carbohydrate intake and sleep quality in men (17). Individuals with disordered sleep (insomnia, obstructive sleep apnea, or a combination of the 2) assessed by questionnaires reported lower total carbohydrate intakes than did normal-weight individuals who were free from sleep disorders.…”
Section: Dietary Patterns and Sleep Qualitysupporting
confidence: 72%
“…In general, those studies indicate higher fat intakes with sleep disorders (17) and that following a Mediterranean dietary profile is associated with fewer insomnia symptoms in women (18). Information on the association between carbohydrate intakes and sleep quality is conflicted (15)(16)(17), with studies reporting low intakes in those with insomnia symptoms (16,17) but high intakes of sweets (15).…”
Section: Dietary Patterns and Sleep Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations have also shown that adults who havebetter sleep quality or who are free of insomnia engaged in a greater amount of habitual exercise, compared to their counterparts with worse sleep quality or insomnia [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Az alvásminőség és egészség-magatartás összefüggését vizsgálták más kutatók is hasonló eredményekkel [15][16][17].…”
Section: Megbeszélésunclassified